Karakterisasi senyawa kompleks dengan logam transisi pada mikropartikel bunga cempaka (Magnolia champaca (L.) Baill. Ex Pierre) sebagai kandidat potensial nutrasetikal: Characterization of complex compounds with transition metals on microparticles of cempaka flowers (Magnolia champaca (L.) Baill. Ex Pierre) as a potential nutraceutical candidate - Maghfiroh, Khoirin; Utomo, Deny (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2023)
The components of complex compounds containing transition metals play a significant role in regulating the nutraceutical ability for disease prevention and treatment. The bonding of complex molecules with transition metals allows energy to be transferred between complex compounds that enter the body and systems within the body. The aim of this research was to investigate the composition of complex chemical components including transition metals used in the processing of M. champaca flowers for potential nutraceuticals. Transition metal identification (XRF), compound identification (LC-MS), functional group identification (FTIR), crystal character identification (XRD), particle surface morphology identification (SEM), particle size identification (PSA), and identification of physicochemical characters of Niacin complex with transition metals (SwissADME) are among the stages of the study. The results showed that the highest type of transition metal was Fe, containing to 0.42%, Niacin group compounds identified were Nicotinic acid and Nicotinamide, in the region 505 - 405 cm-1, there is a transition metal bond with a Fe (Fe - O) functional group, solid particles in M. champaca microparticles were amorphous, peak peaks at an angle of 2Éµ 19,83Â°, Particle morphology is similar to powder on its surface, particles measuring 208.20 Âµm. The physicochemical properties of the Niacin complex with transition metals demonstrate that niacin group chemicals have different effects on nicotinic acid and nicotinamide. These complex chemicals are generally easily absorbed by body systems. Since the synthesis of niacin complexes with transition metals has improved physicochemical properties, it could be employed as a possible nutraceutical candidate.